The Impact of Extreme Climate Events on the American Continent: Causes, Consequences, and Adaptation Strategies - Lola Bianca (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Climate change is a global phenomenon that has led to an increase in the frequency and intensity of extreme weather events. The American continent, spanning from the Arctic to the Antarctic, is particularly vulnerable to these changes. This paper examines the impacts of extreme climate events, such as hurricanes, wildfires, droughts, and heavy rainfall, on both North and South America. We analyze the underlying causes of these events, including anthropogenic factors and natural climate variability, and explore their consequences on ecosystems, economies, and human health. By reviewing recent data and case studies, we identify the most affected regions and sectors. Furthermore, this paper discusses various adaptation strategies implemented across the continent, evaluating their effectiveness and proposing improvements. Our findings emphasize the importance of integrated approaches that combine scientific research, policy-making, and community engagement to enhance resilience against future climate challenges. The study aims to contribute to the ongoing discourse on climate adaptation and provide actionable insights for stakeholders at all levels.